An aerodynamic characterization facility for micro air vehicle research. Issue 2 (June 2016) - Hart, Adam; Sytsma, Michael; Ukeiley, Lawrence
The Aerodynamic Characterization Facility is a unique facility located at the University of Florida's Research and Engineering Education Facility designed with the intent to study complex low Reynolds number, unsteady aerodynamic phenomena. This facility includes an open jet, open return wind tunnel specifically designed to operate in the low Reynolds number regime where current research efforts are being tasked for Micro Air Vehicle flight platforms. Specifically, the wind tunnel operates with freestream velocities ranging from nominally 0 to 22 m/s with 0.1 m/s resolution provided by a variable frequency drive utilized to control the tunnel. The test section entrance is 1.07 m 2 with a length of 4.6 m. Flow uniformity investigations at free stream velocities of 2 and 4 m/s demonstrate a uniform flow core throughout the test section of at least 50% of the 1.14 m 2 contraction exit. Hot wire anemometry investigations present turbulence intensities less than 0.22% for free stream velocities greater than 1 m/s. The facility is also equipped with a dynamic motion rig and active turbulence generator. The dynamic motion rig is utilized to investigate unsteady aerodynamics over dynamic kinematic motions similar to what one might find in small birds and insects. The active turbulence generator provides a means to introduce atmospheric-like turbulence into the wind tunnel to understand the coupling between turbulence and unsteady flow phenomena associated with bird and insect flight.